Raman imaging of twist angle variations in twisted bilayer graphene at intermediate angles. (1st October 2022) - Schäpers, A; Sonntag, J; Valerius, L; Pestka, B; Strasdas, J; Watanabe, K; Taniguchi, T; Wirtz, L; Morgenstern, M; Beschoten, B; Dolleman, R J; Stampfer, C
Abstract: Van der Waals layered materials with well-defined twist angles between the crystal lattices of individual layers have attracted increasing attention due to the emergence of unexpected material properties. As many properties critically depend on the exact twist angle and its spatial homogeneity, there is a need for a fast and non-invasive characterization technique of the local twist angle, to be applied preferably right after stacking. We demonstrate that confocal Raman spectroscopy can be utilized to spatially map the twist angle in stacked bilayer graphene for angles between 6.5 ∘ and 8 ∘ when using a green excitation laser. The twist angles can directly be extracted from the moiré superlattice-activated Raman scattering process of the transverse acoustic (TA) phonon mode. Furthermore, we show that the width of the TA Raman peak contains valuable information on spatial twist angle variations on length scales below the laser spot size of ∼500 nm.